Tales of an American hobo - Fox, Charles Elmer (Singular lives., 1989)
"Reefer Charlie" Fox rode the rails from 1928 to 1939; from 1939 to 1965 he hitched rides in automobiles and traveled by foot. From Indiana to British Columbia, from Arkansas to Texas, from Utah to Mexico, he was part of the grand hobo tradition that has all but passed away from American life. He camped in hobo jungles, slept under bridges and in sand houses at railroad yards, ate rattlesnake meat, fresh California grapes, and fish speared by the Indians of the Northwest. He quickly learned both the beauty and the dangers of his chosen way of life. One lesson learned early on.